"Rotationous" Grazing Management target, efficiency of pasture utilization, and enteric methane emissions by dairy cattle - Marín, Alejandra (2017)
he Climate Food and Farming (CLIFF) Research Network is an international research network that helps to expand young researchers' knowledge and experience working on climate change mitigation in smallholder farming. CLIFF provides grants for selected doctoral students to work with CGIAR researchers affiliated with the Standard Assessment of Mitigation Potential and Livelihoods in Smallholder Systems (SAMPLES) project. This presentation is "Rotationous" Grazing Management target, efficieny of pasture utilization, and enteric methane emissions by dairy cattle by Alejandra Marin, a CLIFF student with CCAFS Low Emission Development.